2008
DOI: 10.1016/j.ejvs.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cerebrospinal Fluid S100 and Lactate to Predict Clinically Evident Spinal Cord Ischaemia in Thoraco-abdominal Aortic Surgery

Abstract: An increase of C-lactate occurs much earlier than the increase in C-S100 in patients with SCI. Both parameters may be used to adjust protective and therapeutic measures intra- and postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
0
39
1
Order By: Relevance
“…This protein is secreted in large quantities following the acute phase of brain trauma and ischaemia. Khaladj et al studied 13 patients undergoing elective thoracoabdominal aneurysm surgery, and of these 2 developed spinal cord injury [29]. In the patients that developed spinal cord ischaemia there was a strong correlation between S100β and lactate levels in the CSF compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is secreted in large quantities following the acute phase of brain trauma and ischaemia. Khaladj et al studied 13 patients undergoing elective thoracoabdominal aneurysm surgery, and of these 2 developed spinal cord injury [29]. In the patients that developed spinal cord ischaemia there was a strong correlation between S100β and lactate levels in the CSF compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…However, although there is a good correlation to spinal cord ischaemia and rises in CSF lactate, there is a lag between its rise and development of CSF lactate [25]. There is now considerable interest with respects to specific biomarkers that can be biochemically analysed and are more sensitive to spinal cord ischaemia than lactate [26][27][28][29][30][31]. In particular, interest has arisen in the area of protein level monitoring, and so the aim of this work is to determine the ability of EM wave sensors to measure varying quantities of protein.…”
mentioning
confidence: 99%
“…A review of the titles, abstract and the full text resulted in the inclusion of 18 articles. Twelve studies investigated biomarkers in humans [22][23][24][25][26][27][28][29][30][31][32] and six studies investigated biomarkers in animals. [33][34][35][36][37][38] Relatively few studies have been performed in which biomarkers in serum and/or CSF after SCI were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the patients without SCI, significantly elevated (Po0.001) CSF concentrations of S-100b were identified in two patients with ischemic SCI 6 h after unclamping. 32 In another study, significantly elevated serum and CSF concentrations of S-100b have also been identified 6 h after unclamping, compared with patients without SCI. 42 Brunnekreef et al 24 evaluated S-100b CSF concentrations in eight patients who underwent TAAA surgery.…”
Section: 36mentioning
confidence: 99%
See 1 more Smart Citation